The problem of respect in environmental philosophy - Barbora Baďurová (Studia Ecologiae et Bioethicae)
The term respect is frequently used in ordinary communication however it also has a significant role in philosophical discussions focused on environmental ethics. This essay deals with the ambiguity of the term respect. The author analyzes respect from a philosophical point of view claiming that several possible interpretations of what the word respect means and what standards of behavior to which it is to be related. It is pointed out that the issue of whether respect should be understood as an attitude or behavior. The author highlights the problem of constraints imposed by respect and the relation of respect to intrinsic and instrumental value. The approach is analyzed also from the point of view of Kant’s ethics, nevertheless the author examines it also from the standpoints of various contemporary environmental ethicists (e.g. Taylor, Goodpaster, Katz, Lo). However, author concludes that understanding respect as a virtue appears to be a most promising approach in contemporary environmental ethics because it can solve the problem of finding balanced interpretation of respect.